(untitled) (Italian Journal of Public Health, 2007)
The main beliefs relating to the risk assessment of chemicals in foods, new chemicals in raw material as well as in food processing are briefly presented. Evaluation reviews of representative chemicals found in traditional and novel foods are given. Old and new processes or newly recognized compounds, that require careful assessment in terms of their potential human health impact, are discussed. As example of processing-related contaminants, a risk assessment for acrylamide, is described, providing two different approaches in food safety assessment and the management of carcinogenic contaminants.